2011
DOI: 10.1155/2011/128429
|View full text |Cite
|
Sign up to set email alerts
|

Neutron Production in Thick Targets Irradiated with High-Energy Ions

Abstract: The neutron production in thick targets irradiated with 1 GeV protons was studied experimentally, and results are well understood with model calculations, including MCNPX 2.7a. However, one observes very large neutron production rates in the interaction of 44 GeV 12C onto thick Cu-, Pb-, and U-targets beyond calculated rates. The experimental spallation product yield curve in a 20 cm thick Cu target irradiated with 72 GeV 40Ar also cannot be reproduced by several model codes, including MCNPX 2.7a. This may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…The concept of "limiting fragmentation" in spallation reactions does not hold in these thick target interactions any longer. In a preceding publication the enhanced "Neutron production in thick targets irradiated with high energy ions" [2] and radiochemical spallation yields were analyzed using advanced computer simulations such as MCNPX 2.7a. The authors concluded that enhanced neutron production (quote) "may have an impact on radiation safety protection issues for future heavy ion accelerators" under construction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of "limiting fragmentation" in spallation reactions does not hold in these thick target interactions any longer. In a preceding publication the enhanced "Neutron production in thick targets irradiated with high energy ions" [2] and radiochemical spallation yields were analyzed using advanced computer simulations such as MCNPX 2.7a. The authors concluded that enhanced neutron production (quote) "may have an impact on radiation safety protection issues for future heavy ion accelerators" under construction.…”
Section: Introductionmentioning
confidence: 99%
“…Are "hot" He-like projectile fragments responsible for secondary interactions inducing the enhanced neutron emission and enhanced nuclear destruction reported earlier in [1][2][3]? This problem cannot be studied directly with radiochemical methods or neutron yield measurements, but results from these two independent experimental techniques would be useful to obtain a complete picture of this new nuclear process.…”
mentioning
confidence: 99%
“…Rev. C45, 1194 These facts, called "Unresolved Problems" in [6], have been studied further during recent years and published in [7]- [12]. The emphasis of this research has shifted over the years from "Na-production in copper by relativistic ions" to the measurement of excess neutron production which is far beyond theoretical model calculations in THICK Cu targets (or heavier elements such as e.g.…”
Section: Problemmentioning
confidence: 99%
“…The authors know of only one experiment, where massive uranium targets have been irradiated with heavy ions beams, like 44 GeV 12 C. Ref. [7] describes this experiment and shows that the irradiation produced a secondary neutron flux, about a factor of two larger than predicted by any model calculation.…”
Section: Irradiations Of Thick Targetsmentioning
confidence: 99%
“…Several articles have recently appeared describing "unresolved problems" in the study of nuclear interactions in thick targets induced by relativistic ions and their secondary reaction products [1,2]. Product yield distributions in thick copper targets from irradiations with 72 GeV 40 Ar (at the LBNL, Berkeley), 44 GeV 12 C (at the JINR, Dubna), and 48 GeV 4 He (at CERN, Geneva) [3] cannot be understood with well-established theoretical concepts, thus constituting "unresolved problems".…”
Section: Introductionmentioning
confidence: 99%